Impaired autophagy: a link between neurodegenerative and neuropsychiatric diseases - Polajnar, Mira (Blackwell Publishing Ltd, 2014)
Protein misfolding, and subsequent aggregation have been proven as the leading cause of most known dementias. Many of these, in addition to neurodegeneration, show profound changes in behaviour and thinking, thus, psychiatric symptoms. On the basis of the observation that progressive myoclonic epilepsies and neurodegenerative diseases share some common features of neurodegeneration, we proposed autophagy as a possible common impairment in these diseases. Here, we argue along similar lines for some neuropsychiatric conditions, among them depression and schizophrenia. We propose that existing and new therapies for these seemingly different diseases could be augmented with drugs used for neurodegenerative or neuropsychiatric diseases, respectively, among them some which modulate or augment autophagy.